2020
DOI: 10.3389/fpsyt.2020.551808
|View full text |Cite
|
Sign up to set email alerts
|

Frontoparietal Network Connectivity During an N-Back Task in Adults With Autism Spectrum Disorder

Abstract: Conclusions: Our findings suggest that since adults with ASD performed well on the n-back task, their appropriate, but effortful recruitment of alpha-band mechanisms in the frontoparietal network to maintain items in STM and WM may compensate for atypical modulation of this network in the theta band to recognise previously presented items in STM.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(23 citation statements)
references
References 206 publications
(301 reference statements)
0
20
3
Order By: Relevance
“…This can be associated with significant synchronization and temporal coherence dysfunction, decreasing large cortical networks between the two hemispheres from binding temporally and spatially. This can result in a functional disconnection syndrome ( 88 , 102 , 135 , 137 , 279 , 289 , 290 ).…”
Section: Discussionmentioning
confidence: 99%
“…This can be associated with significant synchronization and temporal coherence dysfunction, decreasing large cortical networks between the two hemispheres from binding temporally and spatially. This can result in a functional disconnection syndrome ( 88 , 102 , 135 , 137 , 279 , 289 , 290 ).…”
Section: Discussionmentioning
confidence: 99%
“…For estimation of task-related power the time-window of interest was 900-1900ms post-stimulus onset (i.e., during the fixation cross of the next trial). This time-window was chosen as existing studies investigating WM-related oscillatory activity typically use the maintenance period of the working memory task as the time-window of interest as increased oscillatory activity is observed during this period [20,24,31,46]. We followed the previous literature’s definition of the maintenance period as the time following a response to the stimuli, determined using the average (or median) response time on the given task [31].…”
Section: Methodsmentioning
confidence: 99%
“…Studies in neurodevelopmental disorders that experience overlapping cognitive impairments with NF1 (e.g., ADHD/ASD [14]) have reported differences in oscillatory activity during working memory performance relative to typically-developing controls [27,28,29,30,31]. For instance, Jang et al [28] found significantly reduced theta power in ADHD relative to controls.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Because of this effect on cognitive functioning, and the important role that cognitive functioning plays in helping individuals deal with anxiety-provoking stimuli (Bishop et al, 2004), it is not surprising that disruption in the FPN is also associated with anxiety that emerges from an inability to solve problems and think through challenges, resulting in GAD in particular (Ball et al, 2013;Cui et al, 2016;Etkin et al, 2009;Liao et al, 2013;Sylvester et al, 2012). There is also evidence of an association between disruption of the FPN and SF (Marek & Dosenback, 2018;Ptak, 2011;Scolari et al, 2015) in the non-autistic population, plus some evidence for an altered FPN in the autistic population (Lin et al, 2019;May & Kana, 2020;O'Reilly et al, 2017;Yuk et al, 2020). However, these findings have primarily focused on executive functioning deficits, rather than on SF and GAD specifically.…”
mentioning
confidence: 99%